Inhibiting an Epoxide Hydrolase Virulence Factor from Pseudomonas aeruginosa Protects CFTR. Issue 34 (1st July 2015) - Bahl, Christopher D.; Hvorecny, Kelli L.; Bomberger, Jennifer M.; Stanton, Bruce A.; Hammock, Bruce D.; Morisseau, Christophe; Madden, Dean R.
Abstract: Opportunistic pathogens exploit diverse strategies to sabotage host defenses. Pseudomonas aeruginosa secretes the CFTR inhibitory factor Cif and thus triggers loss of CFTR, an ion channel required for airway mucociliary defense. However, the mechanism of action of Cif has remained unclear. It catalyzes epoxide hydrolysis, but there is no known role for natural epoxides in CFTR regulation. It was demonstrated that the hydrolase activity of Cif is strictly required for its effects on CFTR. A small‐molecule inhibitor that protects this key component of the mucociliary defense system was also uncovered. These results provide a basis for targeting the distinctive virulence chemistry of Cif and suggest an unanticipated role of physiological epoxides in intracellular protein trafficking. Abstract : 'Diol' EH for virulence : The protein Cif is secreted by P. aeruginosa and blocks the endocytic recycling of CFTR, an ion channel required for mucociliary clearance. The ability of Cif to hydrolyze reporter epoxides was shown to be required for virulence, thus indicating a link between epoxides and protein trafficking. A small‐molecule inhibitor that protects this key element of airway defenses was identified and could lead to a new therapeutic approach.